Freedom and equality in democracies: is there a trade-off? - Heiko Giebler; Wolfgang Merkel (International Political Science Review, 2016)
In political philosophy, economic theory and public discourse, there is a seemingly endless debate on what the essence of equality and freedom is and what relation between the two is essential to a good political order. Views range from the conviction that too much socio-economic equality jeopardises freedom to the position that a certain level of equality is necessary for the proper realisation of freedom. Building on these conflicting normative claims, we look at data from more than 50 established and emerging democracies for a period of more than 20 years to investigate whether there is indeed a trade-off between freedom and equality or whether they are mutually reinforcing. In the process, we distinguish between two types of equality – political and socio-economic. Our findings suggest that there is a positive relationship between freedom and both types of equality – even if we control for the level of economic development.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; freedom; political equality; socio-economic equality; trade-off; comparative politics; democracies